Functional Diversification of Populus FLOWERING LOCUS D-LIKE3 Transcription Factor and Two Paralogs in Shoot Ontogeny, Flowering, and Vegetative Phenology - Sheng, Xiaoyan; Hsu, Chuan-Yu; Ma, Cathleen; Brunner, Amy M. (Frontiers in Plant Science, 2022)
Both the evolution of tree taxa and whole genome duplication (WGD) have occurred many times during angiosperm evolution. Transcription factors are preferentially retained following WGD suggesting that functional divergence of duplicates could contribute to traits distinctive to the tree growth habit. We used gain- and loss-of-function transgenics, photoperiod treatments and circannual expression studies in adult trees to study the diversification of three Populus FLOWERING LOCUS D-LIKE (FDL) genes encoding bZIP transcription factors. Expression patterns and transgenic studies indicate that only FDL2.2 promotes flowering and that FDL1 and FDL3 function in different vegetative phenophases. Study of dominant repressor FDL versions indicate that the FDL proteins are partially equivalent in their ability to alter shoot growth. Like its paralogs, FDL3 overexpression delays short day-induced growth cessation, but also induces distinct heterochronic shifts in shoot development — more rapid phytomer initiation and coordinated delay in both leaf expansion and the transition to secondary growth in long days, but not in short days. Our results indicate that both regulatory and protein coding sequence variation contributed to diversification of FDL paralogs that has led to a degree of specialization in multiple developmental processes important for trees and their local adaptation.